Evaluation of Multilateral Based Elementary School Students' Athletic Sports Development Program - Suratmin Suratmin; I Putu Panca Adi; I Putu Darmayasa; Wasti Danardani; Ratna Kumala; Hanik Liskustyowati; Muhammad Fakhrur Rozi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The purpose of the study was to evaluate the multilateral development-based elementary school athletic sports development program in the province of Bali. Evaluation research uses survey methods with qualitative and quantitative descriptive approaches. The number of samples of elementary school students as student sports week athletes (Porjar) in athletic competitions amounted to 55 athletes, while the number of coaches was 13 people. Data were obtained through questionnaires, interviews, observations, archives, and documentation. Data analysis used triangulation of data sourced from elementary school students, coaches, sports stakeholders, archives, and researcher observations. The conclusions obtained are (1) collaboration is formed through a memorandum of agreement (MoA) between the Department of Education and Culture of Elementary Education with the Health and Recreation Physical Education Study Program (PJKR) and the Sports Training Education Study Program (PKO) of the Faculty of Sports and Health (FOK) Undiksha and the All-Indonesian Athletics Association (PASI) in the regency/city of Bali province, (2) setting targets for developing athletic sports for elementary school students according to their developmental age, by balancing academic/non-academic aspects, sports interests/talents, and program adjustments training, (3) developing a recruitment system for gifted students with tests and measurements (anthropometry, bio motor, medical examination, and psychological tests) according to developmental age, (4) competent, reliable trainers, and graduates of sports coaching education, understanding the philosophy of coaching, students’ development, experienced in coaching, and licensed according to the sport they are engaged in, and an (5) form sports class/athletic sports club as the implementation and program of the Regency/City Educational Youth and Sports Office of the province of Bali.